A Review of Authors Research Methods of Articles in the Journal of Hospital over the Past Two Years Running Title: Hospital journal Research Methodology - Abbas Jahangiri; Mohammad Jahangiri (Tehran University of Medical Sciences, 2019)
Background: One of the most important ways to promote the quality and attractiveness of the journal for readers is the accurate evaluation of the published articles research methodology in the journals. The purpose of this study was to investigate the research methods of the articles published in the Journal of Hospital.   Materials & Methods: In this descriptive study, the research methods of all articles published in the Journal of Hospital from Fall 2016 to Fall 2018 including qualitative or quantitative, field or library research , data collection methods, data analysis software, location of research, nature of the research (descriptive or analytical, etc.), topics, as well as the number of authors were investigated.   Results: Data of 55.29% of papers was qualitative that was turned to quantitative, 47.06% of articles had descriptive-analytical method, and 68.24% of papers had employed a field research method. In addition, 51.76% of articles had used questionnaire and the SPSS software was used in 52.08% of the articles. The location of 45.45% of researches was in Tehran province. Finally, the subject of 23.53% of papers was policy making, planning, leadership, and management in hospitals.   Conclusion: Most authors of the articles have followed a very similar research method during the mentioned period. So, creating diversity in the nature of the researches, using other methods of collecting information rather than questionnaires, doing more library research, and not limiting the researches to Tehran province are the most important suggestions for future researchers.